Asset Inequality and Agricultural Growth: How Are Patterns of Asset Inequality Established and Reproduced? - Sabates-Wheeler, Rachel (Washington, DC: World Bank, 2012)
The relationship between distributions of asset inequality, how these distributions are created and maintained, and agricultural growth are explored. The paper studies Ethiopian agriculture to investigate how differential access to productive assets in the agricultural sector, at various levels (regional, community and household), effect inequalities in agricultural outcomes in terms of productivity and poverty. The dominant discourse on agricultural productivity and distribution has been largely focused on input-output relationships, defined and measured with a yardstick specific to economics. In this study, the processes and institutions that link inequality and productivity are explored. In the Ethiopian case, the persistent nature of inequality is causally related to historical choices and path dependency. What is observed is a complex system whereby inequality affects growth which in turn reinforces processes that exacerbate and reproduce inequalities.